Density functional theory investigations on the binding modes of amidoximes with uranyl ions. Issue 7 (18th January 2016) - Yang, Chuting; Pei, Shuqi; Chen, Baihua; Ye, Lina; Yu, Haizhu; Hu, Sheng
Abstract : η 1 -O of tautomerized amidoximes and η 1 -O/η 2 -N–O of anionic amidoximes are all plausible coordination modes for amidoximes in ligating uranyl ions. Abstract : Density functional theory (DFT) calculations have been carried out to examine the relative facilities of different coordination modes of aromatic amidoximes (AO s) with UO2 (NO3 )2 . Various η 1 -, η 2 - and chelated κ 2 -coordination modes of the possible neutralAO, tautomerized neutral (TAO, with the hydroxylic hydrogen transferring to the oximic nitrogen atom) and anionic amidoxime (AAO, formed by the deprotonation ofAO ) were examined. The results indicate that η 1 -O of theTAO and η 1 -O/η 2 -NO ofAAO are the most plausible coordination modes. Three types of uranyl complexes, i.e. UO2 (NO3 )2 (TAO )(AAO ), UO2 (NO3 )2 (AAO )2 and UO2 (EtOH)2 (AAO )2 are the predominant binding structures. The good consistency between the calculation results and the experimental observations verifies the proposed conclusions.